PENERAPAN MODEL KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS VI SD NEGERI 010 KERESEK KECAMATAN GUNUNG TOAR - Akmal Dahni (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This study aims to improve the learning outcomes of Civics students of class VI SD Negeri 010 Keresek. Thisresearch is a classroom action research (PTK) which is carried out senyak two cycles in which each cycle isimplemented with stages, namely planning, pelakasanaan, observation and reflection. The subjects of this studyamounted to 15 students. Learning outcomes obtained from average learning outcomes before action 66.50 witha percentage of 40% increased to 65% with an average of 74 in cycle I. In cycle II increased again to 90% withan average of 83. Results of research in the class VI SD Negeri 010 Keresek proves that the implementation ofcooperative learning model type NHT can improve the learning outcomes of Civics students of class VI SDNegeri 010 Keresek Kecamatan Gunung Toar.